The design of buck-boost DC-DC converter for BMS - Fang, Siqi (Nanyang Technological University, 2023)
The battery is an important power source for most electronic devices. The voltage of a single battery cell is low therefore the battery cells are usually as a group. Different batteries in the same battery group always have a different battery voltage. This may be due to factory manufacture or the different condition of the battery. Once the difference in battery voltage worsens and the battery voltage falls outside the safety operation range, accidents may happen. The battery management is one of the solutions, to monitor and control the battery conditions. The regulator is used in the cell balancing unit of the battery management system to maintain the battery voltage under safety operation range. The input of the dc-dc converter is designed to be 1-3.6 volt which are the upper and lower charging and discharging limit. The output of the converter is a constant 2.5 volt to charge other batteries in the battery group under safety charging condition. The design should also be able to sustain a low voltage drop when a current is drawn from the output. However, the factors required to have a better performance in area, stability and accuracy of circuit may conflict. Hence, the circuit needs to be design carefully to achieve a balance in this aspect and meet the requirement of the project.